New records of the genus Snellenius Westwood, 1882 (Hymenoptera: Braconidae: Microgastrinae) from Vietnam, with description of two new species - Long, Khuat Dang; Achterberg, Kees van (Academia Journal of Biology, 2013)
The small genus Snellenius Westwood, 1882 is newly recorded for Vietnam and two new species are described and illustrated, viz. Snellenius nigellus Long & van Achterberg sp. n. and S. similis Long & van Achterberg sp. n.; one new status is Snellenius theretrae (Watanabe, 1937) stat. n.; two newly recorded species for Vietnam’s fauna are Snellenius philippinensis (Ashmead, 1904) and S. maculipennis (Szépligeti, 1900). The checklist and distribution of seventeen extant species and one fossil species, Snellenius succinalis Brues, 1933, are given, of those four species are described from the Neotropical region and the remaining species are described from Oriental region. A key to the species of the genus Snellenius from Vietnam is provided.